Battling pornography the American feminist anti-pornography movement, 1976-1986 - Bronstein, Carolyn (Cambridge University Press, 2011)
"In the mid-1970s, American feminists formed grassroots organizations to protest the proliferation of advertisements, films, and other popular media that glorified sexual violence against women. They pioneered feminist analyses of these images, which were thought to promote sexist attitudes and behavior, and male power and control. Over time, feminists shifted their focus to pornography, and a full-fledged anti-pornography movement was born. This book analyzes the rise and fall of the American feminist anti-pornography movement, situating its development in the social and cultural history of the late 1960s and 1970s, including the sexual revolution and the second wave. Based on extensive original archival work, Carolyn Bronstein chronicles the three most influential movement organizations and reveals how and why anti-pornography took root. Bronstein shows that the strategic reorientation to pornography propelled the movement into the national spotlight but also ignited a counter-movement led by feminists and free speech advocates that ultimately toppled anti-pornography in the mid-1980s. Battling Pornography offers a detailed account of inner movement dynamics and the contributions of its central actors, including some of the best-known figures in American feminism"--